OP0126 Cd28 directly initiates il-4 gene transcription and induces tcr independent th2 cell differentiation in human memory cd4 t cells. (1st June 2001) - Skapenko, A; Lipsky, PE; Kalden, JR; Schulze-Koops, H
Abstract : Background: Evidence suggests that human autoimmune diseases might be driven by pro-inflammatory Th1 cells whereas immunomodulatory Th2 cells are rarely found. Th1 dominated immunity might result from disordered regulation of memory T cell differentiation with insufficient generation of Th2 cells to down-modulate inflammation. Objectives: To gain insights into the mechanisms regulating human Th2 effector differentiation, we investigated Th2 differentiation in isolated human CD4 pos naive and memory T cells in vitro . Methods: A cell culture system was employed that permitted Th2 cell differentiation after short term priming. The phenotype of freshly isolated and primed T cells was determined by cytometric analysis of intracellular cytokines. Analysis of mRNA was performed using semiquantitative RT-PCR. Results: Th2 cells could be generated from resting cord blood naive CD4 pos T cells by priming with anti-CD3 and anti-CD28. Exogenous IL-4 was not required for Th2 cell differentiation from naive T cells and did only marginally increase Th2 priming efficiency. In striking contrast, co-stimulation of memory T cells through CD3 and CD28 increased Th2 cell frequencies only minimally if at all. When recombinant IL-4 was added during priming, an increase in Th2 effectors was noted. Of marked interest, however, significant Th2 cell differentiation was induced by priming of CD4 pos memory T cells with anti-CD28 in the absence of TCR mediated signals. CD28 induced Th2 cell differentiation was dependent on IL-4 as neutralising of IL-4 inhibited the generation of Th2 effecors. As no exogenous IL-4 was required for CD28 mediated Th2 cell differentiation, the impact of CD28 ligation on IL-4 gene transcription in memory T cells was evaluated. IL-4 mRNA levels increased after CD28 engagement. To distinguish whether the increase in IL-4 mRNA levels after anti-CD28 stimulation resulted from initiation of transcription or from stabilisation of preformed mRNA, purified CD4 pos memory T cells were stimulated with anti-CD28 in the presence or absence of actinomycin D. Actinomycin D completely inhibited the CD28 induced increase of IL-4 mRNA. Furthermore, when actinomycin was added when IL-4 mRNA levels were already increased, IL-4 mRNA levels declined markedly with a half-life of app. 60 min, indicating that the increase in IL-4 mRNA after CD28 engagement is caused to a significant extent by the induction of IL-4 gene transcription. Conclusion: CD28 ligation directly initiated IL-4 gene transcription and induced Th2 differentiation in a TCR independent manner in memory but not in naive T cells. TCR independent generation of Th2 effectors might provide a way to control Th1 dominated cellular inflammation.